Halal cosmetics: trend or obligations? - Azmi, Nor Azrini Nadiha; Elgharbawy, Amal A.M. (Corpus Publisher, 2022)
Halal cosmetics are produced from halal materials in the production facility that is not contaminated by filth materials according to Islamic shariah law. To comply with Islamic ritual regulations, cosmetic products must not only be produced using halal materials but also function effectively holistically. As the Muslim population is expanding widely, the demand for halal cosmetics also keeps growing. Exceptional change has been seen in the rise of Muslim customers and their growing purchasing power. However, some obstacles must be conquered before halal cosmetics are recognized and acknowledged, not only in Muslim countries but worldwide. This short article reviews the opinion of halal cosmetics as a whole.